YCbCr Colour Watermark Embedding in Digital Video for Copyright Protection using Zero Padding - Chawla, P.; Sharma, N. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Digital watermarking is a vital process of shielding the intellectual property and copyright of the digital media. In this paper, a new digital video watermarking algorithm Colour Watermark Embedding Algorithm (CWEA) is proposed. CWEA has two important parts. First, YCbCr colour format is used to insert the variable size watermark. Second, Embedding of detail coefficients of LUMINANCE (Y-luminance) of watermark into the detail coefficients of CHROMINANCE (Cb and Cr- chrominance) of identical frames (I-Frames) of digital video. Data is inserted into the detail coefficients based on the energy of high frequency. A number of tests have been executed for most video-frame manipulations and attacks. All these tests are also performed on CWEA and it provides good results. In this paper, non-blind and semi-blind watermarking systems are used where non-blind watermarking mechanism has been proven to be robust, imperceptible and efficient to protect the copyright of H.264 and MPEG-4 coded video within the video retrieval system.